2016
DOI: 10.1002/2015ja022299
|View full text |Cite
|
Sign up to set email alerts
|

Middle‐ and low‐latitude ionosphere response to 2015 St. Patrick's Day geomagnetic storm

Abstract: This paper presents a study of the St Patrick's Day storm of 2015, with its ionospheric response at middle and low latitudes. The effects of the storm in each longitudinal sector (Asian, African, American, and Pacific) are characterized using global and regional electron content. At the beginning of the storm, one or two ionospheric positive storm effects are observed depending on the longitudinal zones. After the main phase of the storm, a strong decrease in ionization is observed at all longitudes, lasting s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
216
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 196 publications
(255 citation statements)
references
References 50 publications
(69 reference statements)
19
216
0
1
Order By: Relevance
“…The crest disappearance at earlier time in Swarm data is also in correspondence to the substorm signature at about 13 UT, related to 19/21 LT depending on the longitudinal sector. This is the result of the F layer shrinking, already reported by Figure 11 of Nava et al [2016]. This is the result of the F layer shrinking, already reported by Figure 11 of Nava et al [2016].…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The crest disappearance at earlier time in Swarm data is also in correspondence to the substorm signature at about 13 UT, related to 19/21 LT depending on the longitudinal sector. This is the result of the F layer shrinking, already reported by Figure 11 of Nava et al [2016]. This is the result of the F layer shrinking, already reported by Figure 11 of Nava et al [2016].…”
Section: Resultssupporting
confidence: 67%
“…The green vertical short lines at the bottom of each plot mean that the ionogram is recorded but the trace is too poor to validate a reliable value of h 0 F. The same gray curve in each of the plots represents the h 0 F values measured at Sanya on 15 March 2015 and here considered as the quiet reference day (analogously toNava et al [2016]). The green vertical short lines at the bottom of each plot mean that the ionogram is recorded but the trace is too poor to validate a reliable value of h 0 F. The same gray curve in each of the plots represents the h 0 F values measured at Sanya on 15 March 2015 and here considered as the quiet reference day (analogously toNava et al [2016]).…”
mentioning
confidence: 99%
“…In order to look for such LTEs in a similar geomagnetic storm category, the author turn to the G4 geomagnetic storm that 25 happened during the St. Patrick's day of 2015, which has been thoroughly studied (Astafyeva et al, 2015;Cherniak et al, 2015;Nava et al, 2016;Yao et al, 2016;Jin et al, 2017;Zhang et al, 2018). This storm was also product of a CME an it was reported that the storm sudden commencement was at ∼04:45 UT on March 17, 2015 (Yao et al, 2016).…”
mentioning
confidence: 99%
“…Previous studies have reported the fact, validated by a number of observations, that a significant source of ionospheric disturbances and different storm-time phenomenon (e.g. TID propagation) is Joule heating at high latitudes (de Abreu et al, 2010;Nava et al, 2016;Yao et al, 2017). Due to the impact of magnetic storms of 17 March 2015, the ionosphere appeared characteristics of peaks and troughs.…”
Section: Resultsmentioning
confidence: 86%
“…They found storm-induced LSTIDs which were propagating towards the Equator and had large wave parameters. Nava et al (2016) Figure 1. Location of GPS receiver stations.…”
Section: Introductionmentioning
confidence: 99%